2012
DOI: 10.3109/13693786.2011.574239
|View full text |Cite
|
Sign up to set email alerts
|

Ceratonia siliqua(carob) trees as natural habitat and source of infection byCryptococcus gattiiin the Mediterranean environment

Abstract: Recent Cryptococcus gattii infections in humans and animals, including several outbreaks in goats, were the basis of this environmental survey in six provinces of Spain. A total of 479 samples from 20 tree species were studied. Cryptococcus gattii was found for the first time in autochthonous Mediterranean trees in Spain. Fourteen isolates of this pathogen were obtained from seven trees of three different species: 12 from carob (Ceratonia siliqua), one from Mediterranean stone pine (Pinus halepensis) and anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 30 publications
2
55
1
1
Order By: Relevance
“…Significant difference was seen in the isolation frequency of C. neoformans and C. gattii during autumn and rainy season (P < 0.001) and spring and rainy season (P < 0.001) respectively. Colom et al [2] also reported low rate of isolation of each pathogenic Cryptococcus species from Eucalyptus trees. This is also in accordance with previous finding from Mediterranean area [7,8,18].…”
Section: Discussionmentioning
confidence: 93%
“…Significant difference was seen in the isolation frequency of C. neoformans and C. gattii during autumn and rainy season (P < 0.001) and spring and rainy season (P < 0.001) respectively. Colom et al [2] also reported low rate of isolation of each pathogenic Cryptococcus species from Eucalyptus trees. This is also in accordance with previous finding from Mediterranean area [7,8,18].…”
Section: Discussionmentioning
confidence: 93%
“…Besides host immune factors, pulmonary cryptococcosis could also be related to environmental exposure to contaminated airspace, including close contact with animals [16][17][18][19], green plants [20] or other natural sources contaminated by fungi [21].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the differentiation between C. neoformans and C. gattii is a difficult task since: the available commercial differentiation methods (e.g., API ® 20C AUX [bioMérieux, France], Vitek ® [bioMérieux] and MicroScan ® [Siemens, Germany]) do not differentiate between C. neoformans and C. gattii; and the methods capable of differentiating the two species (multiplex PCR, liquid array detection of pathogens, PCR restriction fragment length polymorphism [12,13] and matrix-assisted laser desorption/ionization mass spectrometry future science group of continental North America. The potential for C. gattii to cause illness in immunocompetent patients and its rapid spread worldwide justify the implementation of a public health effort to increase the awareness of both the public and healthcare professionals [1,[18][19][20][21][22][23][24]. The mechanism of C. gattii dispersion is not well understood.…”
mentioning
confidence: 96%